Clinical and surgical specifications of adult unilateral diaphragmatic eventration according to their aetiology in 28 patients. Importance of using diaphragmatic patch and minimal thoracotomy incision - Balci, Akin Eraslan; Ozyurtkan, Mehmet Oguzhan (Elsevier Science Bv, 2010)
Objective: This study aims to determine the differences among various diaphragmatic eventration (DE) aetiologies and to compare the outcomes of the operation relative to the use of a diaphragmatic patch. Methods: Between 2003 and 2009, 28 patients with a DE who underwent surgery were classified according to the following aetiology: (a) previous operation or disease, (b) congenital/idiopathic and (c) trauma. Patients who received diaphragmatic patches during their operations (plication + patch, P/P, 19 cases) were compared with the patients receiving sole plication during the operation (P, 9 cases). The operations had been performed through a minimal length lateral thoracotomy incision (12-14 cm). Results: The mean age of the patients was 53.3 +/- 9.8 years. A high hemi-diaphragm (atone or associated with a blunt sinus or a wide mediastinum) was the most prominent chest X-ray (CXR) finding in 19 patients (68%). The postoperative mean forced expiratory volume in 1 s (FEV(1)) value (2.1 +/- 0.7) and the dyspnoea score (1.8 +/- 0.7) were better than the preoperative values (1.7 +/- 0.6; 3.4 +/- 0.9, respectively). The average height of the diaphragm (7.8 +/- 3.1 cm) was not correlated with the dyspnoea score and the FEV(1) value. Postoperative complications (4/28 or 14.3%) were minimal, excluding one respiratory insufficiency. The mean follow-up time was 23.4 +/- 17.8 months. Patients with congenital aetiology were younger, had higher diaphragms, had earlier operations after symptoms started and had better preoperative FEV, values. P/P operations were done later than P operations. The P/P method patients had shorter postoperative hospital stays than the P method patients. Two diaphragmatic events (recurrence and herniation) occurred after the operations were performed with the P method. Conclusions: Buttressing the diaphragm by patch after the plication can protect from recurrence of a DE or any diaphragmatic insufficiency. Previous abdominal interventions may increase the complication rate after a DE operation. (C) 2009 European Association for Cardio-Thoracic Surgery. Published by Elsevier B.V. All rights reserved.
Keywords: Diaphragmatic eventration; Plication; Patch